Bending stiffness of Candida albicans hyphae as a proxy of cell wall properties. Issue 20 (12th September 2022) - Couttenier, Elodie; Bachellier-Bassi, Sophie; d'Enfert, Christophe; Villard, Catherine
Abstract : Hydrodynamic forces applied in a microfluidic device on hyphae of C. albicans allow to measure their bending stiffness in a control situation as well as under various pharmacological, mechanical and genetical perturbations. Abstract : The cell wall is a key component of fungi. It constitutes a highly regulated viscoelastic shell which counteracts internal cell turgor pressure. Its mechanical properties thus contribute to define cell morphology. Measurements of the elastic moduli of the fungal cell wall have been carried out in many species including Candida albicans, a major human opportunistic pathogen. They mainly relied on atomic force microscopy, and mostly considered the yeast form. We developed a parallelized pressure-actuated microfluidic device to measure the bending stiffness of hyphae. We found that the cell wall stiffness lies in the MPa range. We then used three different ways to disrupt cell wall physiology: inhibition of beta-glucan synthesis, a key component of the inner cell wall; application of a hyperosmotic shock triggering a sudden decrease of the hyphal diameter; deletion of two genes encoding GPI-modified cell wall proteins resulting in reduced cell wall thickness. The bending stiffness values were affected to different extents by these environmental stresses or genetic modifications. Overall, our results support the elastic nature of the cell wall and its ability to remodel at the scale of the entire hypha over minutes.